Subtitling Neapolitan Dialect in “My Brilliant Friend”: Linguistic Choices and Sociocultural Implications in the Screen Adaptation of Elena Ferrante’s Best-selling Novel - Cordisco, Mikaela; De Meo, Mariagrazia (Respectus Philologicus, 2022)
In the screen adaptation of Elena Ferrante’s best-selling novel “My Brilliant Friend”, the first foreign language co-production of the American pay-cable network HBO with the Italian public broadcaster RAI, as a specific requirement of the American producers, the Italian of the main characters has been transformed into Neapolitan, a thick regional dialect mostly appropriate to tell the story of a life-long friendship on the backdrop of the 1950s poor outskirts of Naples, the main city of southern Italy. Starting from some background theories of cultural aspects of translation together with audiovisual translation, the aim of this presentation is that of analysing how English subtitlers have faced the translation of the dialectal elements in such a culture-bound audiovisual text and to what extent their choices depend on those made by Italian subtitlers, then discussing about the sociocultural implications of the solutions adopted. The data have been organized and presented with reference to the extralinguistic and the intralinguistic levels (in terms of syntactical, lexico-semantic and crosscultural pragmatic elements).